Comparative outcome of socket shield method and conventional immediate implant implantation with immediate temporization- a 10 years follow-up - Khan, Abdullah Al Mamun; Zahan , Nasrin Parvin (International Journal of Research in Medical Sciences, 2023)
Background: Dental implants are now regarded as an effective treatment option for replacing missing teeth. The objective was to evaluate the socket shield approach with immediate temporization to the conventional instantaneous implant with immediate temporization utilizing the parameters of horizontal and vertical dimensional bone loss, crestal bone thickness (CBT) and pink esthetic score (PES). Methods: This prospective study was carried out at Banasree Dental and German Dental implant surgery centers from December 2010 to December 2020 where 74 patients who had non-restorable maxillary teeth in the esthetic region were conducted and evaluated for implant settlement. The allocated individuals were divided into two groups immediate implant with socket shield group (study group, n=22) and the conventional immediate implant placement group (control group, n=52). SPSS version 21.0 was used to analyze all of the data. Results: Mean value of crestal bone thickness (CBT) at the pre-operative time was 1.31±0.2 in both groups but at the 6 months follow-up time it was 1.2±0.22 and 1.07±0.21, at the 24 months follow-up time it was 1.13±0.24 and 0.99±0.20 and at the 60 months follow-up time in was 1.05±0.27 and 0.79±0.15 and at the 120 months follow-up time it was 1.03±0.29 and 0.69±0.17 in the study and control group respectively. In the study group, the mean value of pink esthetic score was 11.45±1.6 at 6 months follow-up time, 12±0.89 at 24 months, 12.5±0.87 at the 60 months and 12.5±0.86 at the 120 months follow-up time whereas in the control group, it was 11±1.32, 10±1.52, 8.9±1.63 and 7.5±1.55, respectively. Conclusions: The SST group revealed minimal reduction in CBT, horizontal and vertical bone loss and a superior PES compared to conventional immediate implant.